KEPENTINGAN EKONOMI RWANDA DALAM PERANG KONGO - Arinaldo Habib Pratama (Andalas Journal of International Studies (AJIS), 2018)
This research is conducted to understand how Rwanda is able to achieve their economic interest in Congo War,using national interest and resource wars as main concept . The result of research shows that Rwanda is able to achieve their economy interest because either Democratic Republic of Congo was unable to grasp political, security and also economy control. The emergences of mineral world market during Congo War also contribute to Rwanda‟s economy interest during Congo War. Although Rwanda‟s economic interest in DRC could be categorized as form of illegal economy, Rwanda able to convince international community and Rwanda‟s people because security threat that come from inside Zaire or DRC.Keyword : Rwanda, Congo War, economy interest, resource wars, mineral exploitation